1997
DOI: 10.1046/j.1365-2222.1997.1310936.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major water/salt insoluble wheat proteins involved in cereal hypersensitivity

Abstract: Individuals who are hypersensitive to water/salt soluble wheat proteins produce specific IgE to water/salt insoluble wheat proteins. Western blotting has shown that gliadins, glutenins and proteins with similar molecular weights as the endogenous water/salt soluble wheat enzyme inhibitors are important allergens. Alpha and fast omega- are the most allergenic gliadins. The water/salt insoluble proteins share cross-reacting epitopes with water/salt soluble proteins. These data show that the numbers of proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 0 publications
2
57
0
Order By: Relevance
“…Repetitive sequences of gliadin proteins are closely related to their allergenic properties (Sandiford et al 1997). In IgE mediated allergies a specific IgE class antibodies (sIgE), present in elevated amounts in sera of allergic people, bind with epitopes-short amino acid sequences-of allergenic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive sequences of gliadin proteins are closely related to their allergenic properties (Sandiford et al 1997). In IgE mediated allergies a specific IgE class antibodies (sIgE), present in elevated amounts in sera of allergic people, bind with epitopes-short amino acid sequences-of allergenic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of wheat gliadins and low molecular weight (LMW) glutenins, termed WGG, was prepared by a modified method of Sandiford et al 12 Wheat flour was extracted twice with 0.5 M NaCl for 1 h, washed twice with distilled water, and then extracted with 70% ethanol. The ethanol extract was then dried by a centrifuging evaporator and dissolved with 10% dimethyl sulfoxide.…”
Section: Methodsmentioning
confidence: 99%
“…IgE recognizes linear 5~10 amino acid sequences of allergen proteins, which are termed epitopes. Among many wheat allergen proteins, gliadins and glutenins have been well studied [10][11][12] . Tanabe et al identified a glutenin epitope (QQQPP) 15 and gliadin epitopes (PQQPF and QQPFP) 16 for atopic dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of OA are elicited by IgE-mediated respiratory sensitization to both water-soluble and water-insoluble cereal proteins contained in flour (54,55). However, flour from other sources, such as buckwheat (56), Lathyrus sativus (57), and soybean (58), may also cause OA.…”
Section: Cereal Flour and Dustmentioning
confidence: 99%